ANALISIS DAYA SAING SEKTOR UNGGULAN DALAM STRUKTUR PEREKONOMIAN KABUPATEN MIMIKA - Ahmad Usman Ali; Abu Bakar (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2018)
This study aims to determine the leading sector of economic and find the competitiveness among economic structures ofMimika Regency. Descriptive methodologyis used to describes something. Data collection using documentation and library method. To know the superior sectors and competitiveness of the leading sectors, the analysis instruments using LQ analysis to find out the leading sectors in the economic stucture of mimika and shift share district to determine the competitiveness of superior sectors. The result of this study indicate that there are 13 leading sectors in the Mimika region, namely agriculture, forestry and fisheries, electricity and gas procurement sector, water supply, waste management waste and recycling, construction, large and retail trade, car and motorcycle repairs, transportation and warehousing, provision of accomodation and feeding, information and communication of financial services and insurance, real estate, corporate services government administration, defense and social security, and other services. And there are four sectors in mimika that have competitiveness, namely agriculture, forestry, and fishery sector, electricity and gas procurement sector, water supply of waste recycling waste management, goverment administration sector, defense and social security.